PENGEMBANGAN MEDIA FLASH PLAYERÂ® UNTUK MENINGKATKAN MINAT MELANJUTKAN STUDI PESERTA DIDIK SMP - Pertiwi, Divasari Ardi; Sutarno, Sutarno; Sutarno, Sutarno (Universitas Sebelas Maret, 2014)
This research aims at: (1) producing career information materials on high school through college mediation output assisted flash player®; (2) testing the effectiveness of career information materials on high school through college mediation output assisted flash player® to increase students? interest in further study of Junior High School students in Surakarta. The data were collected through interviews and the scale of interest in further study. The data analysis techniques employed were descriptive qualitative analysis, descriptive statistics and t-test techniques. The results of expert and practitioner tests indicate that the career information materials on high school through college mediation output assisted flash player® is considered good and is appropriate to use. The results of more extensive field testing (testing the effectiveness of the product) showed an increase in students' interest in further study of 21.66 % between the supply of information before and after administration of information materials.